Boas práticas de expressão artística no âmbito da integração e da articulação-curricular - Pessanha, Ana Maria, 1957- (2017)
This paper aims at defending good practices in the context of interdisciplinary curriculum articulation, involving all classes of pre-school and first grade of basic education, where students with Special Educational Needs (NEEcp), with diversified needs, had been integrated in schools of the Schools of Pinhal de Frades, in Seixal, during the biennium 2012/2014. For this purpose, it was made use of plastic arts and drama activities in a relaxed and experimental pedagogic atmosphere, allowing for the valorization of new educational concepts and expressions, promoting the creation of puppets representing several characters. Students created so-called "Bisnaus" puppets, which were designed in order to acquire the basic expressiveness and animation needed to develop symbolism. It was hence possible to create characters, which permitted to communicate in their faces the basic expressions of happiness and affection, related with the expressive, cognitive and affective domains